Thermophysiologies of Jurassic marine crocodylomorphs inferred from the oxygen isotope composition of their tooth apatite. (13th January 2020) - Séon, Nicolas; Amiot, Romain; Martin, Jeremy E.; Young, Mark T.; Middleton, Heather; Fourel, François; Picot, Laurent; Valentin, Xavier; Lécuyer, Christophe
Abstract : Teleosauridae and Metriorhynchidae were thalattosuchian crocodylomorph clades that secondarily adapted to marine life and coexisted during the Middle to Late Jurassic. While teleosaurid diversity collapsed at the end of the Jurassic, most likely as a result of a global cooling of the oceans and associated marine regressions, metriorhynchid diversity was largely unaffected, although the fossil record of Thalattosuchia is poor in the Cretaceous. In order to investigate the possible differences in thermophysiologies between these two thalattosuchian lineages, we analysed stable oxygen isotope compositions (expressed as δ 18 O values) of tooth apatite from metriorhynchid and teleosaurid specimens. We then compared them with the δ 18 O values of coexisting endo-homeothermic ichthyosaurs and plesiosaurs, as well as ecto-poikilothermic chondrichthyans and osteichthyans. The distribution of δ 18 O values suggests that both teleosaurids and metriorhynchids had body temperatures intermediate between those of typical ecto-poikilothermic vertebrates and warm-blooded ichthyosaurs and plesiosaurs, metriorhynchids being slightly warmer than teleosaurids. We propose that metriorhynchids were able to raise their body temperature above that of the ambient environment by metabolic heat production, as endotherms do, but could not maintain a constant body temperature compared with fully homeothermic ichthyosaurs and plesiosaurs. Teleosaurids, on the other hand, may have raised their body temperature by mouth-gape basking, as modern crocodylians do, and benefited from the thermal inertia of their large body mass to maintain their body temperature above the ambient one. Endothermy in metriorhynchids might have been a by-product of their ecological adaptations to active pelagic hunting, and it probably allowed them to survive the global cooling of the Late Jurassic, thus explaining the selective extinction affecting Thalattosuchia at the Jurassic–Cretaceous boundary. This article is part of the theme issue 'Vertebrate palaeophysiology'.